A view on the mechanism of metalloporphyrin degradation in hydrogen peroxide epoxidation reactions - Serra, A. C. (2004)
The stability of biomimetic catalysts is an essential characteristic for them to be of some practical use. The study of the reaction of metalloporphyrin catalysts in hydrogen peroxide oxidations in the presence of benzoic acid allowed to understand whether an intramolecular or intermolecular mechanism is operative in catalyst degradation. Under certain reaction conditions, the presence of a radical inhibitor minimises the catalyst degradation, and therefore, improves the catalytic process.